PENGARUH PRESTASI BELAJAR IPAS TERHADAP AKTIVITAS BELAJAR SISWA DENGAN METODE DEMONSTRASI - Surya Dwi Armada; Muhardila Fauziah (STKIP Subang, 2024)
This study aims to determine the effect of science learning achievement on student learning activities when using the demonstration method at SD N Suryodiningratan 2 during the PLP 2 program. The research employs a quantitative approach with a correlational design. Data were collected through tests and observation sheets, and analyzed using statistical techniques to identify the relationship between science achievement and learning activities. The findings indicate that there is a significant positive correlation between students' science learning achievement and their active participation in learning activities using the demonstration method. This suggests that the demonstration method effectively enhances student engagement and academic performance in science subjects.